2004
DOI: 10.1021/jp0471812
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adsorbed Water on Phonon and UV-Induced IR Absorptions of TiO2 Photocatalytic Particle Films

Abstract: The role of adsorbed water in photocatalytic processes on TiO 2 surfaces has been addressed using ATR-IR spectroscopy. Changes in the IR spectra of thin films of Degussa P25 TiO 2 photocatalyst have been observed in the presence of adsorbed water and under near-UV light. Removal of adsorbed water results in the appearance of absorption peaks at 828, 745, and 685 cm -1 attributed to TiO 2 surface phonon modes. UV irradiation of the dry TiO 2 results in a broad IR absorption which toward lower wavenumbers increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 49 publications
15
85
0
Order By: Relevance
“…A good examination of electron trapping is reported by the recent review of Henderson [16]. The electron trapping energy could range between 0.1 and 1 eV [14,17], in agreement with photoemission results for electronic defects on the surface of TiO 2 single crystal surfaces [18].…”
supporting
confidence: 73%
“…A good examination of electron trapping is reported by the recent review of Henderson [16]. The electron trapping energy could range between 0.1 and 1 eV [14,17], in agreement with photoemission results for electronic defects on the surface of TiO 2 single crystal surfaces [18].…”
supporting
confidence: 73%
“…Overall this leads to an increased photodegradation rate of adsorbed organic compounds. In this case, the broad IR absorption due to trapped electrons [14] can be regarded as an indicator of electron-hole pair separation and organic pollutant photodegradation efficiency.…”
Section: Photodegradation and Electron Transfer On Au@tio 2 During Uvmentioning
confidence: 99%
“…As most important finding it was shown that under certain reaction conditions cyanide is formed, which can adsorb on the gold and even lead to leaching the latter. ATR-IR has also been used to study the band gap irradiation of TiO 2 particle films in contact with water [14]. Vibrational bands below 1000 cm −1 that appeared upon UV illumination were first assigned to surface peroxo or hydroperoxo species [15].…”
Section: Introductionmentioning
confidence: 99%
“…Infrared absorption induced by band-gap excitation provides a quantitative measure of the excited electrons that are still separated in semiconductor photocatalysts such as NaTaO 3 [6][7][8] and TiO 2 [9][10][11][12][13]. In our earlier study [4], the four photocatalysts were excited in vacuum by using a Hg-Xe lamp, and the steady-state electron population was quantified by electron-induced infrared light absorption.…”
Section: Resultsmentioning
confidence: 99%